The Impact of Contextual Clues on Semantic Preference Among Linguistic Differences (Al-Furqan Interpretation by Al-Sadiqi, d. 2011 - Shaheed , Suhad reda (Thi Qar Arts Journal, 2024)
A text is a collection of meaningful and communicative speech events. Understanding a text relies on various clues, with the contextual clue being one of the most crucial. It is a fundamental criterion that determines the value of the intended word in guiding the coherence of texts to convey meaning effectively. A literary text is a beautiful tapestry of words and phrases that flow in an organized and harmonious structure, addressing one or multiple topics. This performance stands out from everyday speech and non-literary writing through its aesthetic qualities, which rely on imagination, rhythm, imagery, suggestion, and symbolism. Therefore, the contextual clue is considered an important entry point for studying and determining meaning. Quranic interpreters have used it to prefer one word over another.